Prevalence and related factors of TB/HIV co-infection among hospitalized children with tuberculosis in Southwest China - Wang, Dong-Mei; An, Qi; Yang, Qing; Liao, Yi (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThis study aimed to investigate the prevalence of TB/HIV co-infection in pediatric TB patients in southwest China and its associated variables.MethodsPediatric TB patients were recruited from January 2014 to September 2024 in southwest China, based on etiology or clinical confirmation. Hospitalization records were extracted for each patient.ResultsAmong 2,607 pediatric TB patients with an average age of 9.58 ± 4.08 years, 39 (1.5%) were HIV-positive. The TB/HIV co-infection group male-to-female ratio was 2:1, higher than the TB-only group 1.19:1. The highest proportion of TB/HIV co-infection was in the 5-9 years age group (43.6%), while the 10-14 years age group accounted for the highest proportion of TB-alone cases (57.5%). In terms of population distribution, the Yi ethnic group had the highest proportion of TB/HIV co-infection cases (43.6%), while the Tibetan group had the highest proportion of TB-alone cases (51.1%). Extrapulmonary TB in the TB/HIV co-infection group primarily involved abdominal and pericardial sites, whereas the TB-alone infection group had more cases of lymphadenitis and pleural TB. The length of hospitalization (>14 days) in the TB/HIV co-infection group (74.4%) was significantly longer than in the TB-alone infection group (51.7%). Over the past 11 years, most pediatric TB/HIV co-infection cases were from the eastern-central and southern-central regions of Sichuan, particularly the southern Liangshan Yi Autonomous Prefecture. The number of children with TB-alone infections increased gradually during this period. No significant difference in the number of pediatric TB/HIV co-infection cases was observed over the 11 years.ConclusionPediatric TB/HIV co-infection in southwest China predominantly affects middle-aged and young boys, with a higher co-infection rate than the national average. The central and southern regions of Sichuan have a relatively high proportion of cases. Public health efforts should focus on strengthening awareness, screening, and early diagnosis of TB and HIV in children in high-risk areas to prevent further infections.